To solve the equation, we first need to distribute the constants outside the parentheses.
-8(3x) - 8(6) = 7(-4x) + 7(1)
-24x - 48 = -28x + 7
Next, we combine like terms on each side of the equation:
-24x + 28x = 7 + 48
4x = 55
Finally, we solve for x by dividing both sides by 4:
x = 55 / 4
Therefore, the solution to the equation is x = 55 / 4.
Solve the following equation for xx. Express your answer in the simplest form.
minus, 8, left parenthesis, 3, x, plus, 6, right parenthesis, equals, 7, left parenthesis, minus, 4, x, plus, 1, right parenthesis
−8(3x+6)=
7(−4x+1)
1 answer